Effect Evaluation of Subxiphoid and Intercostal Thymectomy: A Meta-Analysis and Systematic Review - Wang, Hailong; Wang, Miao; Xin, Ning; Wei, Rongqiang; Huang, Kenan (Frontiers in Surgery, 2022)
Background It still remains unclear whether subxiphoid video-assisted thoracoscopic surgery (SVATS) thymectomy is safe and reasonable. This meta-analysis aims at assessing the effectiveness and safety of SVATS for thymoma in comparison with that of intercostal video-assisted thoracoscopic surgery (IVATS) thymectomy. Methods All the relevant data systematically analyzed in this thesis were retrieved from PubMed, the Cochrane Library, web of science, EMBASE, and clinical trials. The time span for data retrieval was from the date of database establishment to March 2022. The outcome indicators include operation time, intraoperative blood loss, duration of postoperative drainage, postoperative hospital days, VAS score on the day of operation, VAS score on postoperative day 3, VAS score on postoperative day 7, postoperative complications were analyzed in our meta-analysis. Results In 13 studies of this paper, there were 1198 cases included in. Among them, 563 cases were treated by SVATS thymectomy and 635 cases by IVATS thymectomy. There was no significant difference in the operation time and the incidence of intraoperative and postoperative complications between SVATS thymectomy and IVATS thymectomy. However, SVATS thymectomy significantly reduced the amount of intraoperative blood loss, postoperative drainage days , postoperative hospital stays and VAS scores after operation. Discussion SVATS thymectomy is safe and feasible, and the perioperative effect is better than IVATS thymectomy to a certain extent, which is worthy of popularization and further research.